Systematic Literature Review on Human Resource Management Effect on Organization Performance - Metasebia Adula; Shashi Kant; Zerihun Ayenew Birbirsa (Goodwood Publishing, 2022)
Purpose: The current study is the outcome of a thorough evaluation of the literature on functionalism in human resource management as it relates to organizational performance. It examines the role of human resource management and looks into various issues with human resource management in firms in such situations. Research Methodology: The theoretical underpinnings are accomplished through a systematic review and subsequent thematic content analysis of literature, including reports from published literature and research papers that have been published. These were critically examined, and the best matching documents were then carefully chosen for inclusion to reach a conclusion. Result: The result emphasizes the necessity for human resource management managers to implement cutting-edge strategies for faculty and staff empowerment so they may traverse the fast-changing environment and perform to their full potential against the odds. To engage stakeholders in amicably avoiding recalcitrance, a conceptual qualitative framework is established and recommended for the functionalism of tailored human resource management. This approach can help managers of human resources find opportunities during this crisis and help them come to significant conclusions about how to address issues and create a positive culture. Limitation: Risks of bias such as selection bias, insufficient blinding, attrition bias, and selective outcome reporting may be among the limitations. Future Implications: By working together to overcome predicted difficulties, this framework can help an educational leader manage stakeholders' expectations and benefit academics and practitioners alike. Novelty: Research novelty was a brand-new concept that might result in new knowledge or contribute to already-existing knowledge.